1998
DOI: 10.1046/j.1365-2141.1998.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate‐stable monosaccharide derivatives induce maturation and apoptosis in human acute myeloid leukaemia cells

Abstract: The rapid degradation and subsequent lack of efficacy of n-butyric acid in vivo has been improved by the synthesis of monosaccharide stable pro-drugs of butyric acid. We studied the effects of D1 (O-n-butanoyl-2,3-O-isopropylidene-alpha-D-mannofuranoside), G1 (1-O-n-butanoyl-D,L-xylitol), and F1 (1-O-n-butanoyl 2,3-O-isopropylidene-D,L-xylitol) on the maturation and proliferation of AML cell lines HL 60 and FLG 29.1 and of purified blast cells from 10 cases of de novo acute myeloid leukaemia (AML). AML cell ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In fact, although butyrate arrests normal cells in G 1 , it induces apoptosis in transformed cells within 4 hours after G 1 -S arrest. 58,[65][66][67][68][69][70][71][72][73][74][75][76][77] Thus, the activities of butyrate that cause cell cycle arrest may be problematic when the drug is used in patients with hemoglobinopathies unless it is given intermittently, which, in turn, limits the amount of ␥-globin and the proportions of F cells that can be induced.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although butyrate arrests normal cells in G 1 , it induces apoptosis in transformed cells within 4 hours after G 1 -S arrest. 58,[65][66][67][68][69][70][71][72][73][74][75][76][77] Thus, the activities of butyrate that cause cell cycle arrest may be problematic when the drug is used in patients with hemoglobinopathies unless it is given intermittently, which, in turn, limits the amount of ␥-globin and the proportions of F cells that can be induced.…”
Section: Discussionmentioning
confidence: 99%
“…These effects show no correlation with previous signs of differentiation (i.e., FAB classification). Butyrates are another group of drugs that seem to induce gene expression via histone hyperacetylation, and monosaccharide butyrate derivatives can also induce differentiation in native AML blasts for a subset of patients [41].…”
Section: Altered Histone Acetylationmentioning
confidence: 99%
“…6 Other monosaccharide prodrugs of butyrate have demonstrated similar ability to induce apoptosis of fresh myeloid leukemia cells. 19 A high concentration of butyrate (5 mM) has also been shown to induce apoptosis accompanied by an increase in the level of hsp 70 protein expression in the Burkitt lymphoma cell line BL-30 after 16 h of exposure. 7 Of interest, butyrate-induced apoptosis in HL60 cells was correlated with decrease in bcl-2 protein expression, suggesting that one mechanism for the butyrate-mediated effects observed in leukemia cells may be related to effects of butyrate on expression or function of anti-apoptosis genes.…”
Section: Figurementioning
confidence: 99%
“…Recently Santini et al 19 reported that the butyrate monosaccharide ester, MAG=3 induced apoptosis in HL60 cells without overexpression of the known apoptotic regulatory genes, c-myc and p53, but with decrease in bcl-2 expression. Perhaps the induction of apoptosis in HL60, K562, and other cell lines expressing anti-apoptosis genes represents a selective sensitivity of these cells to the effects of butyrates to modulate expression of genes important in cellular homeostasis.…”
Section: Figurementioning
confidence: 99%